‘When I use the electric wheelchair, I can be myself’ – real-life stories about occupational identity construction - Maria Lindström; Ann-Charlotte Bäckström; Catharina Henje; Gunilla Stenberg (Scandinavian Journal of Occupational Therapy)
Background Young and adult users of electric wheelchairs (EWs) describe how EWs have personal, functional, emotional, and symbolic values and are considered by some to be part of the self.Aim The aim of this study was to increase our understanding of how occupational identity is constructed in the daily practices of EW users.Material and methods Context-based, in-depth oral stories and filmed sequences of daily practice enactments of persons who have used an EW since childhood were the basis for the narrative analysis.Findings The findings elucidate how the informants enact and tell about their identity-development in response to daily and relational practices, and its relevance to the informant’s sense of self, belonging, competence, life-prospects, conduct, and awareness of shifting values, and this was likewise demonstrated in different appearances and roles related to social recognition. A model illustrating the findings is proposed.Conclusions and significance Contextual values and exploring experiences, such as possibilities to develop competences and roles, along with encountering social recognition, but also hindering regulations and adversities, influence the development of occupational identities. Findings in this study can contribute to increased understanding, conscious political decisions, as well as a more person-centred approach within healthcare.